PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP NIAT BELI MASYARAKAT SEBAGAI KONSUMEN BIG TV PADA KELURAHAN SEI AGUL KECAMATAN MEDAN BARAT - Sitanggang, Darna (UNIKA Santo Thomas, 2016)
The rise of information technology today, resulted in viewers want more information forms from abroad in the form of news and entertainment shows. The need for more extensive information, an opportunity for the satellite television station. Satellite TV is not to compete with each other is BIG TV, which is one of the satellite TV channel highest and the lowest in Indonesia, both SD (standard definition) and HD (high definition), while becoming a satellite TV pay-first serving HD channels more lots for its customers. From the description, the problem in this research is formulated as follows: